Routine postoperative nasogastric or nasojejunal tube placement may be unnecessary after gastric resection - Alemdar, Ali; Yeşiltaş, Metin (The European Research Journal, 2023)
Objectives: The purpose of this study was to investigate the effects of not using routine nasogastric (NG) or nasojejunal (NJ) tubes on postoperative complications in gastric cancer patients undergoing resection. Methods: This study includes 250 patients who underwent gastric resection diagnosed with gastric adenocarcinoma between November 2011 and December 2021. The patients were divided into two groups: those who routinely use NG or NJ tube in the early postoperative period and those who do not. Postoperative complications and length of hospital stay were compared between the two groups. Results: Demographic, surgical, and histopathological characteristics were similar between the two groups. Oral feeding was started earlier in the non- NG or NJ tube group. There was no difference between the two groups regarding the length of hospital stay (p = 0.065). Severe postoperative complications (Clavien Dindo ≥ 3) were significantly lower in patients who did not use a nasogastric or nasojejunal tube (p = 0.001). Two patients in the NG/NJ tube group and one in the non-NG/NJ tube group developed anastomotic leakage. Conclusions: According to the results of our study, routine NG or NJ tube use does not reduce postoperative severe complications or length of hospital stay.